Study of Scrap Waste in Kathmandu Valley - Luitel, Kishor P; Khanal, Sanjay Nath (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Scrap wastes are the wastes which are the part of the solid waste, segregated and taken further for reusing and recycling from the mixed waste. This scrap waste is called the Kabadi Waste in Nepal. The objective of this study is to identify the scrap waste material and assess collection and business activity of scrap waste generated with in Kathmandu Valley. Direct observations, formal and informal discussion, field study with questionnaire were used for data acquisition. 33 random samples, out of 178 scrap shop were selected for study. During the period of this study waste from transfer station was not allowed to collect by outsiders except by the employed person of the municipality. The composition of scrap waste consisted of 32.49% glasses, 23.89% papers, 22.65% plastics and others (metals, textile, leather and rubber) 20.97%. Among those reusable material consisted of 38.96% and 44.77% was recyclable materials; remaining could be either recycled or reused. 41% of scrap waste collection was done through door to door by cycle hawker. 53% of the scrap waste was found recycled or reuse in Nepal. Similarly, 45% of scrap dealers processed scrap for further recycling. 36% of the Kabadi shop has employed less than 10 people for the waste collection. Now, people from lower casts were also found involved in this business. This study clearly indicates the significance of scrap waste which is a part of Municipal Solid Waste. Keywords: Solid Waste; Recycle; Reuse; Trade of Secondary Material; Scrap; Kabadi. DOI: 10.3126/kuset.v6i1.3319 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp116-122